Synthesis and characterizations of ZnO nanoflowers prepared by one step microwave assisted solvothermal route for optoelectronic applications - Rai, Ravi S.; Pant, Ruby; Chaudhary, Shristi; Gupta, Rupesh; Yadav, Chandrmani (Physics and Chemistry of Solid State, 2026)
In this study, blossom-shaped ZnO nanoflowers (NFs) were successfully synthesized using a rapid, one-step microwave-assisted solvothermal method with zinc nitrate hexahydrate and hexamethylenetetramine as precursors. The synthesis was completed within five minutes, relying solely on inexpensive reagents and eliminating the need for costly additives or high-temperature furnaces, thereby providing an efficient and economical route. Structural analysis through X-ray diffraction confirmed the high crystallinity of the ZnO NFs, while field emission scanning electron microscopy revealed their characteristic blossom-like morphology with an average particle size of approximately 18 nm. Optical properties were investigated by UV–visible spectroscopy, where a sharp absorption peak near 348 nm indicated good monodispersity. The optical band gap was determined as 3.22 eV using Tauc’s relation, which is significantly lower than that of bulk ZnO (3.51 eV), demonstrating a red shift. Moreover, the computed Urbach energy of 0.34 eV reflects low structural disorder in the nanostructures. The combination of rapid synthesis, controlled morphology, high crystallinity, and favorable optical characteristics underscores the novelty and strong potential of these ZnO nanoflowers for future optoelectronic and photonic device applications.